Extreme ocean : amazing animals, high-tech gear, record-breaking depths, and much more! - Earle, Sylvia A., 1935-; Phelan, Glen (National Geographic kids., 2020)
Photographs and text explore the ocean ecosystem, how scientists explore and study it, environmental threats, and major disasters in or caused by oceans. Includes a glossary, resources for further research, and an index.